Digital farmer profiling helps farmers access finance - Rwakigumba, Ronald (Technical Centre for Agricultural and Rural Cooperation, 2018)
Ronald Rwakigumba, Agricultural finance specialist, explains how having farmer digital profiles has enabled agricultural organisations access finance and increase profitability.